Integritas Laporan Keuangan : Analisis Terhadap Pengaruh Ukuran Kap, Manajemen Laba Dan Dewan Komisaris Independen - Sekar Ayu Rizkandari; M. Imam Sundarta; M. Anwar Masruri (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Financial statements are the primary means of conveying financial information to stakeholders; therefore, they must possess a high degree of integrity so as not to mislead users. The integrity of financial statements reflects the reliability and honesty of the information presented, which can be influenced by various factors such as the size of the public accounting firm (PAF), earnings management practices, and the presence of an independent board of commissioners. This study aims to analyze the influence of the size of the PAF, earnings management, and the independent board of commissioners on the integrity of financial statements. This study employs a quantitative approach with an associative research design. The study population consists of companies listed on the Indonesia Stock Exchange, with purposive sampling used to determine the research sample. The data used are secondary data in the form of companies’ annual financial statements. Data collection was conducted through documentation, while data analysis utilized multiple linear regression and classical assumption tests. The results indicate that the size of the public accounting firm does not have a significant effect on financial statement integrity. Meanwhile, earnings management has a significant negative effect on financial statement integrity, whereas an independent board of commissioners has a significant positive effect on financial statement integrity. Simultaneously, all independent variables have an effect on financial statement integrity. This study concludes that earnings management practices can undermine the integrity of financial statements, whereas oversight by an independent board of commissioners can enhance that integrity. Consequently, companies need to strengthen their corporate governance and reduce opportunistic practices to maintain investor confidence.